Effect of pH of colloidal suspension on crystallization and activation energy of deep levels in SnO2 thin films obtained via sol-gel - Ravaro, Leandro P. [UNESP]; dos Santos, Dayse I. [UNESP]; Scalvi, Luis Vicente de Andrade [UNESP] (Pergamon-Elsevier B.V. Ltd, 2009)
Colloidal suspensions of tin dioxide (SnO2) are prepared by the sol-gel method from suspensions with distinct pHs. The particles in solution are embedded by an electrical layer. Decreasing the pH contributes to the destruction of this layer, leading to a high degree of aggregation among particles (clusters) due to the generation of cross-linked bonds (Sn-O-Sn) between them. The aggregation affects the electrical properties of films deposited by dip-coating from these solutions, due to the higher packing produced by acid pH. The X-ray diffractograms of films indicate higher crystallinity for lower pH. The Arrhenius plot leads to activation energies of the deepest level, which was between 67 and 140 meV, for the films prepared from suspensions with pH 6-11. Lower pH films also presented higher electrical conductivity. Obtained activation energies may be related to different types of defects, which could be associated with oxygen vacancies with distinct neighborhoods, influenced by the pH and potential barriers between grains, due to distinct packing caused by cross-linked bonds. TGA/DTA results indicate an easier crystallization process for lower pH, which ends at lower temperature, in good agreement with X-ray diffraction data. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Oxides; Semiconductors; Sol-gel growth; Thermogravimetric analysis (TGA); Electrical properties